Analysis of Susceptibility to the Antimicrobial and Anti-Biofilm Activity of Human Milk Lactoferrin in Clinical Strains of Streptococcus agalactiae With Diverse Capsular and Sequence Types - Lu, Jacky; Guevara, Miriam A.; Francis, Jamisha D.; Spicer, Sabrina K.; Moore, Rebecca E.; Chambers, Schuyler A.; Craft, Kelly M.; Manning, Shannon D.; Townsend, Steven D.; Gaddy, Jennifer A. (Frontiers in Cellular and Infection Microbiology, 2021)
Group B Streptococcus (GBS) is one of the leading infection-related causes of adverse maternal and neonatal outcomes. This includes chorioamnionitis, which leads to preterm ruptures of membranes and can ultimately result in preterm or stillbirth. Infection can also lead to maternal and neonatal sepsis that may contribute to mortality. Currently, treatment for GBS infection include a bolus of intrapartum antibiotic prophylaxis to mothers testing positive for GBS colonization during late pregnancy. Lactoferrin is an antimicrobial peptide expressed in human breast milk, mucosal epithelia, and secondary granules of neutrophils. We previously demonstrated that lactoferrin possesses antimicrobial and antibiofilm properties against several strains of GBS. This is largely due to the ability of lactoferrin to bind and sequester iron. We expanded upon that study by assessing the effects of purified human breast milk lactoferrin against a panel of phenotypically and genetically diverse isolates of GBS. Of the 25 GBS isolates screened, lactoferrin reduced bacterial growth in 14 and biofilm formation in 19 strains. Stratifying the data, we observed that colonizing strains were more susceptible to the growth inhibition activity of lactoferrin than invasive isolates at lactoferrin concentrations between 250-750 µg/mL. Treatment with 750 µg/mL of lactoferrin resulted in differences in bacterial growth and biofilm formation between discrete sequence types. Differences in bacterial growth were also observed between capsular serotypes 1a and III. Maternally isolated strains were more susceptible to lactoferrin with respect to bacterial growth, but not biofilm formation, compared to neonatal sepsis isolates. Finally, high biofilm forming GBS strains were more impacted by lactoferrin across all isolates tested. Taken together, this study demonstrates that lactoferrin possesses antimicrobial and antibiofilm properties against a wide range of GBS isolates, with maternally isolated colonizing strains being the most susceptible.